Macro-economic model of the Guyanese economy. - Ganga, Gobind Nauth (1990)
Formulates and estimates a macro-economic model for the Guyanese economy by emphasising import dependence and the growth of output. Acknowledges that the policy simulation has shown that the model could be a good tool for examining policy alternatives.